Adaptive routing strategy in multi layer satellite communication networks - LI Hui; GU Xue-mai (Tongxin xuebao)
The characteristics of multi-coverage of multilayer satellite networks make sure of good validity and reliability of the space-based networks.Walker delta type constellation guarantees permanent inter satellite links between satellites in the same layer and provides nonpermanent inter orbit links,both of which make an autonomic satellite backbone.Un-der statistic model of traffic flow from global perspective,multilayer satellite networks consider path delay and ISL link weight adopt adaptive routing strategy and bear more reliability.Compare with single layer satellite networks,multilayer satellite networks distribute traffic more evenly and have smaller percent of lost packet,network normalized link load and total path weight of special path,which do favor to decreasing percent of blocking probability of network and the special path.